Analisis Faktor-Faktor yang Mempengaruhi Efisiensi Pengisian E-Spt PPN pada KPP Pratama Batam - Windi Daun La'bi; Erni Yanti Natalia (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research, focusing on the Analysis of Factors Influencing the Efficiency of VAT Return Filing at the Pratama Tax Office Batam, concludes the following based on its findings and discussions: Firstly, the partial implementation of e-VAT returns has a positive and significant impact on the efficiency of VAT return filing, as perceived by Taxable Entrepreneurs at the Pratama Tax Office Batam, thereby accepting the first hypothesis. Secondly, the partial influence of e-Invoices (E-Faktur) is also positive and significant regarding the efficiency of VAT return filing, according to the perceptions of Taxable Entrepreneurs at the Pratama Tax Office Batam, thus accepting the second hypothesis. Thirdly, the partial influence of e-VAT return socialization has a positive and significant impact on the efficiency of VAT return filing, as perceived by Taxable Entrepreneurs at the Pratama Tax Office Batam, leading to the acceptance of the third hypothesis. Lastly, the simultaneous implementation of e-VAT returns, e-Invoices, and e-VAT return socialization has a positive and significant impact on the efficiency of VAT return filing, as perceived by Taxable Entrepreneurs at the Pratama Tax Office Batam, thereby accepting the fourth hypothesis. Overall, this research provides insights that the implementation of e-VAT returns, e-Invoices, and e-VAT return socialization can enhance the efficiency of VAT return filing at the Prathama Tax Office Batam, according to the perceptions of Taxable Entrepreneurs.